2006
DOI: 10.1038/nm1444
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of KAI1 on tumor cells with DARC on vascular endothelium leads to metastasis suppression

Abstract: CD82, also known as KAI1, was recently identified as a prostate cancer metastasis suppressor gene on human chromosome 11p1.2 (ref. 1). The product of CD82 is KAI1, a 40- to 75-kDa tetraspanin cell-surface protein also known as the leukocyte cell-surface marker CD82 (refs. 1,2). Downregulation of KAI1 has been found to be clinically associated with metastatic progression in a variety of cancers, whereas overexpression of CD82 specifically suppresses tumor metastasis in various animal models. To define the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
178
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(182 citation statements)
references
References 20 publications
1
178
0
3
Order By: Relevance
“…This response is not mediated by its receptor, Gprotein-coupled receptor 54, suggesting that either a paracrine signalling mechanism or an alternative receptor is important. The tetraspanin protein CD82 (also known as kangai-1), which has a role in adhesion signalling, inhibits mouse melanoma cell metastases when bound to the endothelial cell-expressed ligand DARC (Duffy antigen chemokine receptor, which is also known as CD234) 36 . In vitro analysis implicated tumour cell senescence that was induced by the CD82-DARC interaction as the inhibitory mechanism 36 .…”
Section: Metastasis Suppressors and Host Geneticsmentioning
confidence: 99%
“…This response is not mediated by its receptor, Gprotein-coupled receptor 54, suggesting that either a paracrine signalling mechanism or an alternative receptor is important. The tetraspanin protein CD82 (also known as kangai-1), which has a role in adhesion signalling, inhibits mouse melanoma cell metastases when bound to the endothelial cell-expressed ligand DARC (Duffy antigen chemokine receptor, which is also known as CD234) 36 . In vitro analysis implicated tumour cell senescence that was induced by the CD82-DARC interaction as the inhibitory mechanism 36 .…”
Section: Metastasis Suppressors and Host Geneticsmentioning
confidence: 99%
“…D'autres études rapportent que l'activité anti-métastatique de KAI1 pourrait être due à l'inhibition de l'activation de MET ou de la kinase Src [29]. Récemment, l'équipe de K. Watabe a montré que la fonction anti-métastatique de KAI1 dépendait d'une interaction directe entre KAI1 des cellules tumorales et le récepteur DARC présent à la surface des cellules endothéliales, induisant une inhibition de la prolifération et la sénescence des cellules tumorales, et ainsi la suppression des métastases [30]. En effet, l'injection intraveineuse de cellules de mélanome B16F10 surexprimant KAI1 à des souris invalidées pour DARC induit la formation de métastases pulmonaires alors que l'injection de ces mêmes cellules à des souris sauvages inhibe la dissé-mination métastatique, suggérant que la fonction anti-métastatique de KAI1 est dépendante de la présence de DARC.…”
Section: A Carcinome In Situunclassified
“…[2][3][4] Ectopic expression of KAI1 suppresses the metastatic phenotype of AT6.1 and LNCaP prostate cancer cells and of B16BL6 melanoma cells in experimental animal models. [5][6][7] In line with this, human prostate cancer and melanoma cell lines of metastatic origin lack expression of KAI1. 8 Therefore, KAI1 is widely perceived as a metastasis suppressor and has been suggested to represent a promising biomarker for the metastatic potential in human malignancies.…”
mentioning
confidence: 66%
“…13 However, attempts at elucidating how KAI1 inhibits tumor growth and formation of metastases have recently made significant progress. 7,9,14 Bandyopadhyay et al demonstrated that KAI1 mediates growth-suppressive signals, which lead to induction of p21 and inhibition of tumor cell proliferation in response to stimulation with an agonistic anti-KAI1 antibody or an appropriate interacting protein like DARC. 7,9 In addition, KAI1 interferes with activation of the tyrosine kinase cMet resulting in a reduction of invasiveness of human prostate cancer cell lines.…”
mentioning
confidence: 99%
See 1 more Smart Citation